Software para análise de dados experimentais de uma técnica de medida baseada em ressonadores Fabry-Pérot - Amaral, Douglas Ramos do (Universidade Federal de São Carlos, 2023)
This study presentas a software to analize data form a straightforward and non-destructive interferometric technique for measuring the propagation loss in single-mode optical glass waveguides by exploiting a Fabry–Perot cavity effect. The software is useful for understanding the contribution from unwanted effects due to extra-cavities.
Software for the experimental data analysis from a waveguide characterization tecnique with multiple Fabry-Pérot cavities
Keywords: Fotônica; Guia de onda; Medida de perdas; Técnica Fabry-Pérot; CIENCIAS EXATAS E DA TERRA::FISICA::FISICA DA MATERIA CONDENSADA